2021
DOI: 10.3389/fbinf.2021.704157
|View full text |Cite
|
Sign up to set email alerts
|

StartLink and StartLink+: Prediction of Gene Starts in Prokaryotic Genomes

Abstract: State-of-the-art algorithms of ab initio gene prediction for prokaryotic genomes were shown to be sufficiently accurate. A pair of algorithms would agree on predictions of gene 3′ends. Nonetheless, predictions of gene starts would not match for 15–25% of genes in a genome. This discrepancy is a serious issue that is difficult to be resolved due to the absence of sufficiently large sets of genes with experimentally verified starts. We have introduced StartLink that infers gene starts from conservation patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…To get additional test sets we used the following approach. In our previous work (Gemayel et al 2021) we have shown that predictions of gene starts made by StartLink+ have low error rates, ~1%. Therefore, we used StartLink+ to make computational predictions of gene starts in 427 genomes including 108 archaeal, and 319 bacterial ones (104 Enterobacterales,111 Actinobacteria,and 104 FCB group).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…To get additional test sets we used the following approach. In our previous work (Gemayel et al 2021) we have shown that predictions of gene starts made by StartLink+ have low error rates, ~1%. Therefore, we used StartLink+ to make computational predictions of gene starts in 427 genomes including 108 archaeal, and 319 bacterial ones (104 Enterobacterales,111 Actinobacteria,and 104 FCB group).…”
Section: Methodsmentioning
confidence: 97%
“…To eliminate influence of GeneMarkS-2 we consider only the group of genes with starts inferred from the protein alignment evidence. Further on, in this group we selected genes whose starts coincided with predictions of StartLink+ (Gemayel et al 2021) supposed to have error rate ∼ 1%. This set was designated as T 3 .…”
Section: Methodsmentioning
confidence: 99%